2019
DOI: 10.5217/ir.2018.00101
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corticosteroid use on inpatients with inflammatory bowel disease and positive polymerase chain reaction for Clostridium difficile

Abstract: Background/Aims Optimal management of inflammatory bowel disease (IBD) with concomitant Clostridium difficile infection (CDI) is controversial, especially when CDI diagnosis is made by polymerase chain reaction (PCR) testing, which may reflect colonization without infection. Methods We performed a multicenter review of all inpatients with IBD and PCR diagnosed CDI. Outcomes included length of stay, 30- and 90-day readmission, colectomy during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Pretreating mice with anti-TNF-α monoclonal antibodies was associated with more severe histopathology of the colon relative to untreated mice [30]. In addition, NSAIDs, H2-receptor blockers and steroids have all been associated with higher risk of CDI in several retrospective studies [16][17][18][19][30][31][32][33][34]. Notably, several other studies demonstrated no correlation between the aforementioned drugs and the development of CDI [35][36][37].…”
Section: Studies Supporting the Risk Of Using Antiinflammatory Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreating mice with anti-TNF-α monoclonal antibodies was associated with more severe histopathology of the colon relative to untreated mice [30]. In addition, NSAIDs, H2-receptor blockers and steroids have all been associated with higher risk of CDI in several retrospective studies [16][17][18][19][30][31][32][33][34]. Notably, several other studies demonstrated no correlation between the aforementioned drugs and the development of CDI [35][36][37].…”
Section: Studies Supporting the Risk Of Using Antiinflammatory Agentsmentioning
confidence: 99%
“…In addition, a beneficial outcome other hand, inflammation was found to play an important role in the primary protection against CDI and hence suppressing the inflammation through the use of antiinflammatory drugs has been considered a risk factor for CDI [13][14][15]. Therefore, several non-steroidal antiinflammatory drugs (NSAIDs), antihistamines and corticosteroids were associated with higher risk of CDI [15][16][17][18][19]. Experimentally, NSAID-(indomethacin-) pretreated mice had an exaggerated CDI [20].…”
Section: Introductionmentioning
confidence: 99%
“…A combination of two or three immunomodulators was associated with negative outcomes on multivariate analysis [ 146 ]. In a study performed by Lim et al, corticosteroids use following CDI diagnosis by PCR in UC-hospitalized patients was associated with an increased length of hospitalization, higher ICU admission and colectomy rate [ 147 ]. In another retrospective analysis, corticosteroid escalation in CDI-IBD was associated with a higher risk of colon surgery within one year of CDI, while immunomodulator and biologic therapy changes did not influence the outcomes [ 148 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Thirty-seven patients (7%) progressed to severe disease, and old age, 2 or more comorbid underlying diseases, and systemic corticosteroid use were identified as risk factors [ 18 ]. Because high-dose corticosteroids increase the risk of respiratory and opportunistic infections in IBD patients [ 61 , 62 ], the BSG guidelines recommend rapid dose reduction (10 mg/wk) if possible [ 34 ]. The Asian Pacific Association of Gastroenterology (APAGE) recommends that dose reduction be considered in patients on prednisolone > 20 mg per day, depending on disease activity.…”
Section: Management Of Ibdmentioning
confidence: 99%